Positionally cloned genes and age-specific effects in asthma and atopy: an international population-based cohort study (ECRHS). Issue 2 (8th December 2009) - Castro-Giner, F; de Cid, R; Gonzalez, J R; Jarvis, D; Heinrich, J; Janson, C; Omenaas, E R; Matheson, M C; Pin, I; Antó, J M; Wjst, M; Estivill, X; et al.
Abstract : Background: Several genes identified by positional cloning have been associated with asthma and atopy, but few findings have been replicated. Age at onset of asthma has been associated with different phenotypic characteristics, and with variants at chromosome 17q21 identified through genome-wide association. This study examined the associations and age-specific effects on asthma, atopy and bronchial hyper-responsiveness (BHR) of five candidate genes previously identified by positional cloning ( ADAM33, PHF11, NPSR1, DPP10, SPINK5 ). Methods: 51 polymorphisms from 2474 participants from 13 countries who took part in the European Community Respiratory Health Survey (1990–2000) were studied. Asthma and age at onset of asthma were assessed by questionnaire data, BHR by methacholine challenge and atopy by specific immunoglobulin E to four common allergens. Results: Significant associations with asthma, atopy and particularly for asthma with atopy were observed for a large region of 47 kb in the NPSR1 gene, even after Bonferroni correction for multiple comparisons (p<0.001). The associations with NPSR1 were stronger in those reporting a first attack of asthma before the age of 15, with statistically significant interactions with age of onset found for three SNPs. The evidence for ADAM33 and BHR and for an age-specific effect of two SNPs in DPP10 and asthma was weaker. Conclusion: This study provides further evidence for an effect of NPSR1 on asthma, atopy and atopic asthma. In addition, this analysis suggests a role for NPSR1 in early-onset asthma driven by the strong effect of this gene on atopic asthma.